Intensifying Hydrogen Spillover for Boosting Electrocatalytic Hydrogen Evolution Reaction - Xu, Hui; Li, Junru; Chu, Xianxu (Chemical record, 2023)
Hydrogen spillover has attracted increasing interests in the field of electrocatalytic hydrogen evolution reaction (HER) in recent years because of their distinct reaction mechanism and beneficial terms for simultaneously weakening the strong hydrogen adsorption on metal and strengthening the weak hydrogen adsorption on support. By taking advantageous merits of efficient hydrogen transfer, hydrogen spillover‐based binary catalysts have been widely investigated, which paves a new way for boosting the development of hydrogen production by water electrolysis. In this paper, we summarize the recent progress of this interesting field by focusing on the advanced strategies for intensifying the hydrogen spillover towards HER. In addition, the challenging issues and some perspective insights in the future development of hydrogen spillover‐based electrocatalysts are also systematically discussed. This review has summarized the recent findings achieved in hydrogen spillover‐based electrocatalysts for boosting HER by highlighting the definition of hydrogen spillover and manifesting the modification strategies for designing them to better suit the application demand in the near future.